Lactic acid production from Kenaf fibre - Anuar, Hazleen; Mel, Maizirwan; Seeni Mohamed, Nurhafizah; Mohd Sidi, Nor Hanis (2010)
Lactic acid is a useful polymer that can be applied in various purposes such as preservative, acidulant, and flavor in food, textile, and pharmaceutical industries, and a raw material for lactate ester, propylene gylcol, 2,3-pentanedione, propanoic acid, acrylic acid, acetalaldehyde, and dilactide in chemical industries. In polylactic acid production, the common starch or cellulose sources which basically used are from food crops sources where their prices are so high resulted in competition with other fields’ demands. As if the raw materials are considerably high, it may result in high cost production of polylactic acid. Indeed, the fermentation technique also have to ensure contribute to less environment effect since it involved chemical solution. Therefore, in this study kenaf fibre waste has offers cost effective of raw material and this kenaf fibre has been treated for Lactobacillus rhamnosus fermentation to produce polylactic acid. The chemical solution used in this study also considered less harm to environment since they are type of organic acid. Hence, this study tried to produce polylactic acid (PLA) that offers cost effective and environmentally friendly. Moreover, the successful obtaining PLA then had been compared to the existing commercial PLA in terms of their properties.